Multidrug Resistant Pulmonary Tuberculosis Treatment Regimens and Patient Outcomes: An Individual Patient Data Meta-analysis of 9,153 Patients - Ahuja, Shama D.; Ashkin, David; Avendano, Monika; Banerjee, Rita; Bauer, Melissa; Bayona, Jamie N.; Becerra, Mercedes C.; Benedetti, Andrea; Burgos, Marcos; Centis, Rosella; Chan, Eward D.; Chiang, Chen-Yuan; et al. (PLoS medicine, 2012)
Treatment of multidrug resistant tuberculosis (MDR-TB) is lengthy, toxic, expensive, and has generally poor outcomes. We undertook an individual patient data meta-analysis to assess the impact on outcomes of the type, number, and duration of drugs used to treat MDR-TB. Three recent systematic reviews were used to identify studies reporting treatment outcomes of microbiologically confirmed MDR-TB. Study authors were contacted to solicit individual patient data including clinical characteristics, treatment given, and outcomes. Random effects multivariable logistic meta-regression was used to estimate adjusted odds of treatment success. Adequate treatment and outcome data were provided for 9,153 patients with MDR-TB from 32 observational studies. Treatment success, compared to failure/relapse, was associated with use of: later generation quinolones, (adjusted odds ratio [aOR]: 2.5 [95% CI 1.1-6.0]), ofloxacin (aOR: 2.5 [1.6-3.9]), ethionamide or prothionamide (aOR: 1.7 [1.3-2.3]), use of four or more likely effective drugs in the initial intensive phase (aOR: 2.3 [1.3-3.9]), and three or more likely effective drugs in the continuation phase (aOR: 2.7 [1.7-4.1]). Similar results were seen for the association of treatment success compared to failure/relapse or death: later generation quinolones, (aOR: 2.7 [1.7-4.3]), ofloxacin (aOR: 2.3 [1.3-3.8]), ethionamide or prothionamide (aOR: 1.7 [1.4-2.1]), use of four or more likely effective drugs in the initial intensive phase (aOR: 2.7 [1.9-3.9]), and three or more likely effective drugs in the continuation phase (aOR: 4.5 [3.4-6.0]). In this individual patient data meta-analysis of observational data, improved MDR-TB treatment success and survival were associated with use of certain fluoroquinolones, ethionamide, or prothionamide, and greater total number of effective drugs. However, randomized trials are urgently needed to optimize MDR-TB treatment. Please see later in the article for the Editors' Summary.